Forest Research Institute Malaysia (FRIM) / Anis Amalyn Amran - Amran, Anis Amalyn (Faculty Of Chemical Engineering, 2022)
This industrial training report of Anis Amalyn binti Amran to undergo an industrial training at FRIM Company within 24 weeks to fulfil the requirements of Apprenticeship (CHE354). The training started from 2l 51 Februa1y 2022 and ended on 4th August 2022 which guided by Mrs Saidatul Husni binti Saidin. The purpose of this program is to fulfil the course order to complete the Diploma as well as graduate from the university. The training refers to work experience that is relevant to professional development prior to graduate. In first chapter this report is defining the term of industrial training and description on industrial training objectives. This part explains the details of objectives of industrial training report and industrial report. In second chapter of report is overview of the company and departments. The third chapter describes the summary of the duties and various tasks in weekly of industrial training activities that carried out. The next chapter explains the details of the tasks given during the industrial training and the experience gained when conducting the activities. In this chapter it also explains about the problem encountered and the adopted solutions to solve the problems. Besides, it also includes the ethics of working at the FRIM company and the ethical issues might occurred during the industrial training. Perhaps, in these details of the tasks given it also explains the health, environmental and sustainable of the company policies applied where it might be related during the tasks execution. This training gives students a good experience m improving self-confidence and responsibilities towards the task given during the internship period. This can be considered as a preparation for students before starting their future career path. In a nutshell, this Integrated Internship Program provides students with various work experiences, work cultures and work values which is crucial for students to begin with their future career path. Last but not least, trainee got opportunities to learn more about the time management whereby with shorter due dates during the internship training which helps trainee to increase their work productivity and· critical thinking when completing the task given. Thus, the trainee also can relate the knowledge that they have learn and applied in real life.